Approximation models for the evaluation of TCP/AQM networks - Dariusz Marek; Adam Domański; Joanna Domańska; Jakub Szyguła; Tadeusz Czachórski; Jerzy Klamka; Katarzyna Filus (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2022)
The article proposes a model in which Diffusion Approximation is used to analyse the TCP/AQM transmission mechanism in a multinode computer network. In order to prevent traffic congestion, routers implement AQM (Active Queue Management) algorithms. We investigate the influence of using RED-based AQM mechanisms and the fractional controller PIγ on the transport layer. Additionally, we examine the cases in which the TCP and the UDP flows occur and analyse their mutual influence. Both transport protocols used are independent and work simultaneously. We compare our solution with the Fluid Flow approximation, demonstrating the advantages of Diffusion Approximation.